正火风冷对20Cr2Ni4A内花键齿轮畸变的影响 - 杨秀兰; 邓凯 (Jixie chuandong)
Analysing various factors effecting the distortion of gears showed that the normalizing proless is a most important factor ,and then having the normalization be improved with a morderute cooling speeds get fime results.